Treatment of acromioclavicular joint dislocation with looped steel plate and clavicular hook steel plate: recent therapeutic observation - Dingtao Li; Zhanshan Zhang; Xiaodong Wang (Journal of the Pakistan Medical Association)
Objective: To compare the clinical efficacy of Endobutton-looped steel plate and clavicular hook steel plate in the treatment of acromioclavicular joint dislocation.